The Influence of Motivation, Knowledge, and Ability to Pay on Compliance in Paying Premiums for Self-Participants in the National Health Insurance Program in West Lombok Regency - Saimi Saimi; Abdul Khaliq; I Nengah Dwi Jendra Atmaja (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Compliance among participants in the self-funded health insurance scheme to pay premiums is crucial to facilitate access to healthcare services. Lack of knowledge, motivation, and the ability to pay are factors contributing to payment arrears. The aim of this research is to identify the factors influencing the compliance of self-funded health insurance participants in paying premiums in West Lombok Regency in 2022. This study is a quantitative research using a cross-sectional design. The population in this study consisted of 50,630 individuals. The research sample included 397 people selected using the Multistage cluster random sampling technique. Data analysis involved univariate and bivariate analysis, with chi-square and logistic regression tests. The research results indicate a correlation between the level of knowledge (0.03), motivation (0.000), and the ability to pay (0.000) with the compliance of self-funded health insurance participants in paying premiums. Meanwhile, the most dominant influencing factor is motivation (p=0.000; OR=32.410). Social Security Administering Agency - Health (BPJS - Kesehatan) is expected to enhance information and socialization efforts among participants regarding the national health insurance program so that the public is motivated to be more compliant in premium payments, and to provide flexible payment options for participants with irregular incomes in the form of installment payments.